OLDER PEOPLE’S EXISTENTIAL LONELINESS FROM THE PERSPECTIVE OF BEING A NEXT OF KIN - Larsson, H. (Innov Aging, 2017)
In the health care context, existential issues are important, in particular when death comes closer as among frail older people. The concept of existential loneliness has been described as a condition of life, an experience and a process of inner growth. However, how existential loneliness is perceived as a phenomenon remains unclear. Listening to the voices of next of kin’s can be one way to reveal older persons’ experience of existential loneliness. Hence, the aim of this study was to explore older persons’ existential loneliness from the perspective of being a next of kin. The study was descriptive with a qualitative design and 16 interviews with next of kin’s were carried out. The data was analyzed using qualitative content analysis. The findings showed that next of kin’s perceived existential loneliness among their relative when mobility and space, were limited, were disconnected from others and were in a process of separation, meaning that they were leaving their lives behind. The findings also showed that next of kin’s perceived that the older person’s experience of existential loneliness could be reduced by social activities and when being cared for in an environment that supports contact with others.